The Role of Virtual Collaboration and Social Capital In the Development of New Products (Case Study: Use of Yammer in XYZ Company) - Lestari, Elissa Dwi (APMBA (Asia Pacific Management and Business Application), 2015)
The theme of this paper is the role of the organization and social capital in the process of virtual collaboration. Business environment is constantly changing and the level of intense competition makes organizations  strive to create more sustainable value. For large organization  with large networks, there are geographical limitations that restrict the process of collaboration between its networks. Advances in technology enable and facilitate the organization to collaborate virtually. From the perspective of dynamic capabilities, virtual collaboration is conceptualized as the dynamic changes in the organization's ability to identify, integrate, and apply knowledge assets as learning materials to meet the competitive demands. Virtual collaboration here enables the process of communication and coordination organization, learning, and innovation-related decision-making processes, and process improvement.This paper uses a case study analysis to explore deeply about virtual collaboration and Social Capital in organization. The result  of the analysis in this paper suggests that engagement, transparency, and horizontal nature of the communication process  can encourage new organizational learning but they can only be done   for  business portfolio. More over, this research also reveals that social capital contributes to the enhancement of organization virtual collaboration process. In addition, cultural factors also limit the success of virtual collaboration on  the distribution of information in the organization at lower levels.